1982
DOI: 10.1177/004051758205200106
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Functional Relationships Between Fiber Properties and the Strength of Open-End Spun Yarns'

Abstract: Using samples from 96 bales of Texas High Plains cotton, multiple regression techniques were used to select the "best" functional expression for the impacts of High-Volume-Instrument-measured fiber properties on the strength of open-end spun yarns. Results indicate that the most important fiber properties are strength, fineness, and length uniformity. Impacts of fiber properties are typically nonlinear. The micronaire value is inversely related to yarn strength and is best expressed as a cubic polynomial.. ABS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…This feature makes these systems very suitable for dealing with the behaviour of non-linear relationships that are common in textile engineering. Neural network models have been applied to many different areas of cotton processing and performance: yarn hairiness (Babay et al, 2004), spinning performance (Beltran et al, 2004;Pynckels et al, 1997), yarn strength (Cheng and Adams, 1995), yarn ten-sile properties (Ramesh et al, 1995) and fabric properties (Fan and Hunter, 1998), and the relationships between fibre properties and the strength of open-end spun yarns (Ethridge et al, 1982). Furthermore, Basu et al (2002) employed an artificial NN to study the relationship between yarn and fabric handling properties.…”
Section: Introductionmentioning
confidence: 99%
“…This feature makes these systems very suitable for dealing with the behaviour of non-linear relationships that are common in textile engineering. Neural network models have been applied to many different areas of cotton processing and performance: yarn hairiness (Babay et al, 2004), spinning performance (Beltran et al, 2004;Pynckels et al, 1997), yarn strength (Cheng and Adams, 1995), yarn ten-sile properties (Ramesh et al, 1995) and fabric properties (Fan and Hunter, 1998), and the relationships between fibre properties and the strength of open-end spun yarns (Ethridge et al, 1982). Furthermore, Basu et al (2002) employed an artificial NN to study the relationship between yarn and fabric handling properties.…”
Section: Introductionmentioning
confidence: 99%
“…They used samples from 96 bales of Texas High Plain cotton to determine the best functional expression for the impacts of High-Volume-Instrument-measured fibre properties on the strength of OE rotor yarns. According to the results, the most important fibre properties determined were strength, fineness, and length uniformity [13]. A report of the International Textile Manufacturers Federation's International Committee on Cotton Testing Methods (ITMF, ICCTM) implied that neps, SFC, dust/trash, maturity and stickiness are influential fibre parameters in an orderly manner.…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies have shown the nonlinear relationship between yarn strength and fiber properties [5]. Since the relationship between yarn strength and fiber properties is nonlinear, it is very difficult to use conventional techniques such regression to predict the yarn strength.…”
Section: Introductionmentioning
confidence: 99%